Rehearsal rooms in the context of norwegian standard ns 8178:2014 - Warzocha Karolina (Technical Transactions, 2021)
Music school students spend much more time rehearsing than performing in concert halls. Individual and small ensemble exercises are a major part of daily practice. The aim of the article is to verify whether the areas of rehearsal rooms given in functional programs attached to architectural contests for music schools, are sufficient to provide required acoustic conditions inside the chamber such as sound power level (SPL) and reverberation time (RT) which is preferred by musicians. The Norwegian Standard NS 8178:2014 was used to calculate the sound level generated by instruments. In this paper, the author will focus on small rehearsal rooms dedicated to individual practice and small practice groups of two or three members.